Cnidome and Morphological Features of Pelagia noctiluca (Cnidaria: Scyphozoa) Throughout the Different Life Cycle Stages - Ballesteros, Ainara; Östman, Carina; Santín, Andreu; Marambio, Macarena; Narda, Mridvika; Gili, Josep-Maria (Frontiers in Marine Science, 2021)
Pelagia noctiluca is considered the most important jellyfish in the Mediterranean Sea, due to its abundance and the severity of its stings. Despite its importance in marine ecosystems and the health problems caused by its massive arrival in coastal areas, little is known about its early life stages and its cnidome has never been described. This study of the morphological and anatomical features throughout the life cycle identifies four early stages: two ephyra and two metaephyra stages. Ephyra stage 1, newly developed from a planula, has no velar canals, gastric filaments or nematocyst batteries. Ephyra stage 2, has velar canals, a cruciform-shaped manubrium and gastric filaments. Metaephyra stage 3 has eight tentacle buds and nematocyst clusters for the first time. Lastly, in metaephyra stage 4, the eight primary tentacles grow nearly simultaneously, with no secondary tentacles. Complete nematocyst battery patterns gradually develop throughout the later life stages. Four nematocyst types are identified: a-isorhiza, A-isorhiza, O-isorhiza and eurytele. Of these, a-isorhiza and eurytele are the most important throughout the entire life cycle, while A-isorhiza and O-isorhiza have a more important role in advanced stages. All nematocysts show a positive correlation between increasing capsule volumes and increasing body diameter of the ephyrae, metaephyrae, young medusae and adult medusae. In the early stages, the volumes of euryteles in the gastric filaments are larger than those in the exumbrella, indicating that the capsule volume is critical in the absence of marginal tentacles, specialized for feeding. This study provides updated information, the most extensive description to date, including high-resolution photographs and schematic drawings of all the developmental stages in the life cycle of P. noctiluca. Additionally, the first cnidome characterization is provided for each stage to facilitate accurate identification of this species when collected in the water column, and to raise awareness of the potential for human envenomation.